Hodnocení finanční situace podniku a návrhy na její zlepšení - Švásta, Ondřej (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Bakalářská práce zkoumá finanční výkonnost zvoleného podniku. Hodnotí situaci podniku převážně z pohledu externího uživatele finanční analýzy a navrhuje řešení na případné zjištěné nedostatky ve finanční situaci podniku.

This bachelor’s thesis examines the financial performance of selected company. It evaluates situation of this company from external viewpoint and proposes solutions for recognized shortcomings of company’s financial situation.
Evaluation of the Business Financial Situation and Proposals to its Improvement
Keywords: Finanční analýza; účetní výkazy; analýza poměrových ukazatelů; finanční výkonnost podniku; obchodní podnik.; Financial analysis; financial statements; financial ratio analysis; financial efficiency of company; trading company.